2002
DOI: 10.1046/j.1523-5394.2002.103009.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Mammogram Follow‐up

Abstract: Study results support the combining of interventions and the practical utility of a clinical decision-making algorithm to determine individualized nonadherence risk and to assign service intensity based on individual need. Problems in locating women for enrollment were experienced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 33 publications
0
87
1
1
Order By: Relevance
“…25,37,38 A number of studies provided detailed descriptions of the design and implementation issues addressed during program development or research study. 19,33,34,37,38 In our qualitative data, navigators and program administrators reported that they addressed barriers by anticipating and resolving patients' problems, often by brokering patient relationships with service providers rather than by providing those services directly. For example, several programs reported helping transport patients to clinics.…”
Section: Do Programs Address Barriers?mentioning
confidence: 92%
See 3 more Smart Citations
“…25,37,38 A number of studies provided detailed descriptions of the design and implementation issues addressed during program development or research study. 19,33,34,37,38 In our qualitative data, navigators and program administrators reported that they addressed barriers by anticipating and resolving patients' problems, often by brokering patient relationships with service providers rather than by providing those services directly. For example, several programs reported helping transport patients to clinics.…”
Section: Do Programs Address Barriers?mentioning
confidence: 92%
“…Navigator programs have been established throughout the United States with support from private foundations, 19,31,32 in conjunction with grants from federal, state, and local government, 29,30,33 and through local initiatives by cancer centers, community-based clinics, and philanthropy. 19,34,35 Freeman et al's program in Harlem targeting "high incidence of late-stage cancer and poor prognostic outcomes of low-income and medically underserved minorities" has served as a paradigm for other navigation programs.…”
Section: How Navigator Programs Are Organizedmentioning
confidence: 99%
See 2 more Smart Citations
“…In the effort to remove barriers, patient navigators connect patients to resources and support systems, assist in the healthcare provider interaction, and streamline appointments and paperwork. 34 Several studies have found navigation to be efficacious in terms of improving both the timeliness of diagnostic resolution, 22,[35][36][37] and the stage at cancer diagnosis. [38][39][40] The largest effort to date to examine the role and benefits of navigation (i.e., to assess the timeliness of diagnosis and treatment, patient satisfaction and quality of life, and cost effectiveness) is the Patient Navigation Research Program (PNRP), a 10-site study funded by the National Cancer Institute, with additional support from the American Cancer Society.…”
Section: Introductionmentioning
confidence: 99%